Information needs for construction companies in South East Asia - Tjoe Foek Soen, Suntoro; Ogunlana, Stephen O.; Pennung Warnitchai; Prapon Phasukyud; German Academic Exchange Service (D.A.A.D) (Bangkok : Asian Institute of Technology, 1993)
Information is a key resource within any business activity. It plays an important role from a before company is established through its operation. Before company is established stage, the information required mainly covers general information which helps the decision maker in making go or no-go decision. When the company starts the operation, however, the information required is the info1mation which supports other management functions to keep the company running. This study is intended to produce the information necessary and to find out the sources of those necessary information, needed before company is established by a foreign constrnction company wanting to do business in the Southeast Asian region. Based on the infonnation flows from the sources through the output info1mation that one management function could produce, the simple graphical model was developed. The model was developed for both stages, which consist of ten management functions. It then was verified in foreign construction companies in Thailand. The result shows that, at before company is established stage, the company requires a lot of information which comes from very disperse sources. This will require a lot of effort, time and money, also it will delay the decision making process. To alleviate the problems, it is suggested to establish a construction information center in the country, which should provide all necessary inf01mation for anybody needing them. For the second stage, after company has been established, inf01mation needed is supplied and used internally
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Construction industry -- Asia, Southeastern -- Information services